وجبة الفطور لدى طفل الروضة وعلاقتها بالادراك (Journal Of Educational and Psychological Researches, 2015)
The right of a child to obtain a sufficient quantity and variety, healthy and safe from the elements in the food and breakfast is one of the most important rights to be able to perform his mental and physical properly and sound. And that not eating breakfast leads to delayed maturation of mental function as well as behavior problems, and that this is happening due to the decline of taken daily for some important nutrients during the first four years of the child's age, also affect the performance of the mental processes, especially (attention, perception, memory) because the child in the process of growth, which is determined by the dimensions of physical, mental and motor and cognitive task at this stage. Research has identified goals Do you know:  1 - cognition in children Kindergarten2 - statistically significant differences in cognition depending on the levels of breakfast (low, medium, high). 3 - correlation between meal Alaftorldy children, Kindergarten according to cognitive variables: stage (first class, second) and sex (male, female). 4 - the differences in the relationship between breakfast with kindergarten children and cognitive variables according to a - stage (first class- second) b - sex (males - females). To achieve the goals of research selected sample of children Riyadh in the city of Baghdad was (420) boys and girls were selected from (12) kindergarten random method Tabiqih rate (35) child of every kindergarten has the researcher calculates the nutrients and energy in the breakfast through outsource laboratories Institute nutrition Research at the Ministry of Health also has built (3) tests mentality is (attention, perception, memory) has offered these three tests on a group of arbitrators, experts and specialists in educational and psychological sciences, who are (15) expert to demonstrate the validity of the items of the scale, has been used researcher indicators of sincerity are (honesty virtual and certified construction) either the stability tests were extracted researcher for each test two types of stability has reached stability coefficient to test the attention in a way re-test (0.73) and the way retail midterm (0.75) and total reliability coefficient fortesting cognition in a way re-test (0.80) and the way retail midterm (0.82) and total reliability coefficient to test the memory in a way re-test (0.76) and the way retail midterm (0.78). In light of the goals of current research and after the application of the tests on the sample and analyze their responses statistically using a test t-for one sample correlation coefficient Point Baacyrial and testing t-testing Zaúa to denote correlation coefficients and analysis of variance test (Scheffe) research found the following results: 1 - The children of Kindergarten eat foods with high nutritional value. 2 - The children of Kindergarten  eat nutritious foods more than non-nutritious foods. 3 - that provide health diets higher energy diets unhealthy. 4 - Enjoy the sample children Kindergarten a ttentively and recognize and remember loud. 5 - the breakfast of high and medium nutritional value covered only children more than the low level of food. 6 - There is no difference between firstclass and second in eating meals of high nutritional value. 7 - no statistically significant differences between males and females in eating a meal high nutritional value and in favor of females.In light of the results of research and the researcher has developed a number of recommendations are: - 1 - Provide nutrition free school for the children of Kindergarten by the Ministry of Education, taking into account the quantity and quality of the nutritional value of the food provided to them. 2 - Attention kids good diet Integrated quality and quantity that contains animal protein through the support of the Ministry of Commerce of the contents of the ration card. 3 - to deepen the culture of food for the families of Iraqi across various media. \ 4 - television to announce a significant effect on the culture and behavior of children, so it was necessary to censor any formal program or diet food advertising on television. 5 - directing media and propaganda that serves food to the goals of health and an emphasis on food with high nutritional value. 6 - Giving children healthy eating habits significantly through the publication of booklets colorful child-oriented distributed free of charge. 7 - on the administration to monitor the development of kindergarten children by measuring the weight, height and head size and comparing the global standard